Discrimination and Multiculturalism in Canada: Exceptional or Incoherent Public Attitudes? - Donnelly, Michael J. (American Review of Canadian Studies, 2021)
In this article, I argue that satisfaction with multiculturalism and support for discrimination in the immigration system are conceptually linked but distinct in the Canadian public's mind. Following a large literature, I make the case that despite a normative assumption of nondiscrimination in the intellectual framework and policy rhetoric of multiculturalism, the public can support discrimination while also supporting multiculturalism. To support this, I present the results of a 2017 survey of Canadians. I show that slightly less than half of respondents are willing to explicitly support discrimination. Next, I show that, when faced with a more complex decision that offers the chance to discriminate, many do so. Finally, I compare experimental results to a nearly identical experiment in the United States, which reveals that Canadian and American respondents discriminate at similar rates.